2004
DOI: 10.1111/j.1365-2559.2004.01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Local invasiveness of ameloblastoma. Role played by matrix metalloproteinases and proliferative activity

Abstract: Our results suggest an interdependent mechanism involving MMPs and proliferation of ameloblastoma cells, which may contribute to the local invasiveness of this tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
112
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 23 publications
21
112
2
4
Order By: Relevance
“…of cases suggest that MMP-1 production by these cells might be associated with tumor cell progression of ameloblastomas. Based on the findings reported by Kumamoto et al 16 and Pinheiro et al, 21 it could be suggested that the MMP-1 expression by OKCs cells observed in our study might be related to a functional role for this protease beyond simple extracellular matrix degradation. In fact, MMP-1 activity is capable of releasing growth factors and cytokines present in the surrounding organic bone matrix.…”
Section: Table II Immunoreactivity To Matrix Metalloproteinases In Osupporting
confidence: 79%
See 3 more Smart Citations
“…of cases suggest that MMP-1 production by these cells might be associated with tumor cell progression of ameloblastomas. Based on the findings reported by Kumamoto et al 16 and Pinheiro et al, 21 it could be suggested that the MMP-1 expression by OKCs cells observed in our study might be related to a functional role for this protease beyond simple extracellular matrix degradation. In fact, MMP-1 activity is capable of releasing growth factors and cytokines present in the surrounding organic bone matrix.…”
Section: Table II Immunoreactivity To Matrix Metalloproteinases In Osupporting
confidence: 79%
“…Moreover, the highest epithelial immunoreactivity to MMP-1 in SOKCs (P Ͻ .05) may help to explain the increased aggressiveness of this lesion, when associated with nevoid basal cell carcinoma syndrome, reported in the literature. 8,10,12 The synthesis and secretion of the proenzyme form of MMP-1 by cultured fibroblasts from OKCs 34 and reports implying a role for MMP-1 in tumor progression 16 and local invasiveness of ameloblastomas, 21 as well as in keratinocyte migration, 18 invasion, and metastasis 20 reinforce the importance of this protease in the OKC biology.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Factors related to the epithelial and mesenchymal components participate in the regulation of the growth of odontogenic cystic lesions and tumors. 1 The altered expression of specific proteins of the extracellular matrix (ECM), associated with the exuberant presence of matrix metalloproteinases (MMPs) and the absence of expression of metalloproteinase inhibitors (TIMPs), may influence the behavior of these lesions. In the case of tumors, this situation contributes to the growth and higher aggressiveness of the tumor.…”
mentioning
confidence: 99%